2009
DOI: 10.1111/j.1439-0523.2009.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional marker-assisted selection for bacterial leaf blight resistance genes in rice (Oryza sativaL.)

Abstract: Evolving high yielding rice genotypes with durable resistance to bacterial leaf blight (BLB) is pertinent considering the extensive damage caused by the disease in most of the rice growing regions. Two high yielding BLB susceptible indica rice cultivars, ÔADT43Õ and ÔASD16Õ popular among farmers and consumers across South India have been introgressed with three BLB resistance genes xa5, xa13 and Xa21 from isoline IRBB60 using functional markers. The F 2 populations of 500 plants from ADT43 · IRBB60 and 806 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 48 publications
2
78
0
Order By: Relevance
“…MAS is a pivotal tool for the pyramiding of such recessive genes in the presence of dominant genes such as Xa4 and Xa7. Successful pyramiding of these genes has delivered very promising results (Perumalsamy et al, 2010). Lack of both genes in commercial cultivars and their presence in the landraces tested in this study proved their erosion during the development of modern basmati rice cultivars.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…MAS is a pivotal tool for the pyramiding of such recessive genes in the presence of dominant genes such as Xa4 and Xa7. Successful pyramiding of these genes has delivered very promising results (Perumalsamy et al, 2010). Lack of both genes in commercial cultivars and their presence in the landraces tested in this study proved their erosion during the development of modern basmati rice cultivars.…”
Section: Discussionmentioning
confidence: 90%
“…Several BB-resistance genes have been identified and characterized in non-aromatic rice and incorporated and pyramided through MAS to develop resistant cultivars (Perumalsamy et al, 2010;Rajpurohit et al, 2010). However, their incorporation into the basmati background impairs the superfine grain quality and aroma of basmati rice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 34 genes (23 dominant and 11 reces sive) have been identified that confer resistance to various strains of Xoo (Chen et al, 2011). Major resistance genes, including Xa4, xa5, Xa7, xa13, and Xa21, have been incorporated into rice cultivars in order to develop new resis tant varieties (Perumalsamy et al, 2010). However, cultivars containing a single ma jor resistance gene proved susceptible due to pathogen mutation.…”
Section: Introductionmentioning
confidence: 99%